ANALYSIS OF EXPLAINING STUDENT SKILLS THROUGH ONLINE PEER ASSESSMENT - Bungawati Bungawati (Lembaga Penelitian Mahasiswa Penalaran UNM, 2023)
This study aims to determine the explaining skill of PGMI students through online peer assesment. Research methods used qualitative research with a descriptive approach.Result of this research of students explaining skill through online peer assesment: (1) using language that easily understand was 97%; (2) mastering material was 90,9%; (3) using examples related to the material was 93,9%; (4) using vocal variations was 75,8%; (5) voice emphasis to certain terms was 69,7%; (6) repeated subject matter was 52,5%; (7) build interaction with students was 97%; (8) Allow student to ask was 51,5% and (9) concluding material was 66,7%. The explaining skill of students through online peer assesment was in “skilled” category. It means explaining skill students in science learning need to improve.